Debate: Prevention and Victim Compensation - Varia, Nisha (Anti-Trafficking Review, 2014)
Afroza, a Bangladeshi woman who worked for sixteen years without getting paid and was not allowed to go home to visit her family. Keni, an Indonesian woman whose employers injured her with a hot iron, leaving disfiguring third-degree burns all over her body. Kartika, an older Sri Lankan woman whose employers made her work around the clock without pay, shaved her head to humiliate her and gouged pieces of flesh out of her arm with knives. These are some of the women whose faces and stories still haunt me after ten years of investigating human rights abuses against migrant domestic workers in Asia and the Middle East.